2009
DOI: 10.1167/iovs.08-1888
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitions of Chloride Transport and Gap Junction Reduce Fluid Flow across the Whole Porcine Ciliary Epithelium

Abstract: The effects of the chloride transport inhibitors on fluid formation across the porcine iris-ciliary body were comparable to that in previous chloride transport studies. The results indicated that fluid secretion by the isolated porcine ciliary epithelium is mainly driven by chloride transport. However, there may be other unidentified ion movements that drive residual FF after chloride transport is inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…5,6,[19][20][21] Recently, we have demonstrated that the stimulation of Isc by cAMP and forskolin in porcine CE 22 are in good agreement with results obtained in human tissue. 23 In this study, we aimed to characterize the expression of Cx isoforms in porcine CE, determine the relative abundance of various Cx, and investigate the functional significance of the most abundant Cx in mediating fluid movement from PE to NPE cells.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…5,6,[19][20][21] Recently, we have demonstrated that the stimulation of Isc by cAMP and forskolin in porcine CE 22 are in good agreement with results obtained in human tissue. 23 In this study, we aimed to characterize the expression of Cx isoforms in porcine CE, determine the relative abundance of various Cx, and investigate the functional significance of the most abundant Cx in mediating fluid movement from PE to NPE cells.…”
supporting
confidence: 81%
“…Based on the results of gene and protein expressions, together with the previous findings showing the crucial role of gap junctions between PE and NPE cells in regulating AH secretion, 6,7 we speculated whether Cx43 was important in transferring fluid from PE to NPE cells leading to AH formation in pigs. To test this hypothesis, we used small interfering RNA (siRNA) to knockdown the expression of Cx43 and determined whether it affected the fluid movement across isolated porcine PE-NPE cell couplets by using the LY dye transfer technique.…”
Section: Effect Of Cx43 Knockdown On Dye Transfermentioning
confidence: 83%
See 1 more Smart Citation
“…Because P2Y 6 receptor activation causes TGFβ production (59, 60), UDP may suppress Cl -secretion by producing both TGFβ and cAMP. Another possible candidate is the gap junction because it mediates intercellular connections between PE and NPE cells, which is essential for transepithelial Cl -transport (56,61). Elevation of cAMP caused intercellular uncoupling between PE and NPE cells (56 ]i.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh bovine corneas with the epithelium scrapped off were used as positive control. Each side of the chamber was filled with Ringer's buffer solution (pH 7.4) [30].…”
Section: Functional Testsmentioning
confidence: 99%